Service Behaviors, Customer Requirements, And Service Usages the Laundry Service in Thailand - Cowling, Orapin; Ahluwalia, Pariya (Journal of the Association of Researchers, 2024)
This quantitative research aimed to analyze the behavior of using services, customer needs and the use of laundromat services in Thailand. The sample group was 400 male and female users aged 15-65 years old and above for laundromat services in Thailand. The data were collected by questionnaires and analyzed using frequency, percentage, mean and standard deviation, including one-way ANOVA test. The multiple comparison test and analysis of independence were used to examine the hypothesis. The results of the study found that the majority of the sample group was female, 65.3 percent, and 30.8 percent were aged between 26-35 years. The need for laundromat services was free products / cash discounts as appropriate at a mean of 4.01 or a high level. The sample group emphasized marketing mix factors. The sales promotion was using 10 services and getting 1 free service in a specified amount at a mean of 4.17 or a high level. The hypothesis testing results found that customers with different demographic characteristics, such as occupation and average monthly income, had different behaviors in using laundromat services, while customers with different monthly incomes gave no different importance to marketing mix factors.